Caracterização bromatológica de frutos e geleias de amora-preta - Souza, Angela Vacaro de [UNESP]; Rodrigues, Ramon Juliano [UNESP]; Gomes, Estevao Perin; Gomes, Gabriel Perin [UNESP]; Vieites, Rogerio Lopes [UNESP] (Soc Brasileira Fruticultura, 2015)
The blackberry fruit is highly perishable and therefore its use is preferentially industrial. However, there is few information in the literature about the effect of products processing made of blackberry. In this study, it was evaluated blackberry fruits and jellies from three different stages of harvest. The aim was the bromatological, quantification of total and soluble pectin and macro and micronutrients from fruits and jellies. The results showed that the blackberry presents a high potential for industrialization since most of the compounds evaluated there were no big changes resulted from the processing.

A amora-preta é um fruto de alta perecibilidade e por isso seu aproveitamento é preferencialmente industrial. Entretanto, há pouca informação na literatura a respeito do efeito do processamento de produtos elaborados a partir da amora. Neste trabalho, foram avaliados frutos e geleias em três estádios de colheita diferentes. O objetivo foi realizar a caracterização bromatológica, a quantificação de pectina total e solúvel e de macro e micronutrientes dos frutos e geleias. Os resultados mostraram que a amora-preta apresenta alto potencial para industrialização, pois em grande parte dos compostos avaliados, não houve grandes alterações decorrentes do processamento.
Bromatological characterization of blackberry fruits and jellies
Keywords: Rubus sp.; Jelly; Food processing; Rubus sp; Geleia; Processamento de alimentos